2006
DOI: 10.1002/ijc.21908
|View full text |Cite
|
Sign up to set email alerts
|

Progressive increase of SCCA‐IgM immune complexes in cirrhotic patients is associated with development of hepatocellular carcinoma

Abstract: About 3-4% of cirrhotic patients develop primary liver cancer every year. Specific serologic markers have not yet been identified for screening of high risk patients. The serpin squamous cell carcinoma antigen (SCCA) is overexpressed in liver cancer and circulating SCCA-IgM complexes have been described in patients with hepatocellular carcinoma (HCC). The aim of the present study was to assess the behavior of SCCA-IgM in relation to HCC development in patients with cirrhosis. A retrospective, longitudinal stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 18 publications
6
74
0
Order By: Relevance
“…been proposed in a prospective study of two groups of cirrhotic patients with or without HCC evolution. In this study, an increase in circulating SCCA-IgM was associated with the development of HCC (11). While conventional serum biomarkers failed in the screening of cirrhotic patients in HCC surveillance programmes, SCCA-IgM has shown promise (12).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…been proposed in a prospective study of two groups of cirrhotic patients with or without HCC evolution. In this study, an increase in circulating SCCA-IgM was associated with the development of HCC (11). While conventional serum biomarkers failed in the screening of cirrhotic patients in HCC surveillance programmes, SCCA-IgM has shown promise (12).…”
Section: Discussionmentioning
confidence: 65%
“…This has been reported for a-fetoprotein (AFP) and des-gcarboxy-prothrombin (DCP), which are conventional serological biomarkers of HCC, and also for the newly described HCC biomarker squamous cell carcinoma antigen (SCCA) (7,8). In addition, the clinical value of SCCA-IgM as a predictive biomarker of evolution of HCC in patients with cirrhosis has been also reported, demonstrating that the increase in serum concentrations over time of SCCA-IgM in patients with cirrhosis was associated to higher risk of development of HCC (11). The behaviour of serum concentrations of SCCA-IgM was studied in two groups of cirrhotic patients with similar clinical profiles at presentation and followed prospectively.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of AFP, measured in parallel in the same serum samples, was not significantly different in patients who developed HCC and in those without liver tumor progression. Accordingly, the predictive value of SCCAIgM variation was found to be significantly better than that of AFP for predicting the progression to HCC (AUC: 0.821 vs 0.654) [51] . These data were in line with another retrospective study performed by Buccione et al [52] .…”
Section: Scca-igm and Antiviral Treatmentmentioning
confidence: 89%
“…The first evidence of the behavior of SCCA-IgM during antiviral treatment with PEG-IFN and ribavirin was obtained from a longitudinal study in 2010 [48] . Giannini et al [48] demonstrated that in patients with HCVrelated cirrhosis who achieved sustained virological [44] Significant increase of SCCA-IgM levels over time in 75% of untreated patients with chronic hepatitis and with histologically proven liver disease progression (fibrosis score increase ≥ 2) after six years of follow-up Martini et al [46] In patients with chronic hepatitis C, SCCA-IgM was found an independent predictor of histologically proven non alcoholic steatohepatitis SCCA-IgM and antiviral treatment Giannini et al [48] In chronic hepatitis C treatment with standard therapy, only patients who achieved sustained viral response showed a significant decrease in median values of SCCA-IgM up to one year of follow-up Fransvea et al [49] Reduction of SCCA-IgM levels during the first month of standard antiviral therapy was an independent predictor of sustained viral response Martini et al [46] Significant reduction of SCCA-IgM, lasting up to 6 mo of follow-up, was observed only in HCV-positive patients with sustained response to standard therapy SCCA-IgM in diagnosis and prognosis of HCC Pontisso et al [51] Significant increase over time of SCCA-IgM only in patients with early cirrhosis (histologically proven) who developed HCC within four years of follow up Buccione et al [52] In HCV-positive patients with overt cirrhosis, SCCA-IgM negativity (cut off ≤ 200 AU/mL) accurately identified patients at low risk of liver cancer development in the subsequent year Beneduce et al [24] SCCA-IgM showed higher sensitivity for the diagnosis of HCC, compared to AFP Pozzan et al [53] In patients with HCC, SCCA-IgM levels were found an independent predictor of survival. A reduction in SCCA-IgM levels was correlated with response to HCC treatment HCV: Hepatitis C virus; HCC: Hepatocellular carcinoma; AFP: Alpha-fetoprotein; SCCA-IgM: Squamous cell carcinoma antigen-immunoglobulins M.…”
Section: Scca-igm and Antiviral Treatmentmentioning
confidence: 99%
See 1 more Smart Citation